2017
DOI: 10.1111/asej.12135
|View full text |Cite
|
Sign up to set email alerts
|

Job Mismatch and On‐the‐job Search Behavior Among University Graduates in Malaysia

Abstract: This paper examines the incidence and the effects of job mismatch on workers' job search behavior while working in Malaysia. Using the 2007 Graduate Tracer Study (GTS-07) dataset, approximately 32 percent of workers were deemed mismatched and 52 percent were actively looking for another job. Using a logit model, the risk of being engaged in on-the-job search activity was higher among the mismatched workers and the magnitude of the effects was greater for the severely mismatched than for the moderately mismatch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…In Developing Countries, to our knowledge, there are only a few studies that have been carried out. These include Mexico (Quinn & Rubb, 2006), Pakistan (Abbas, 2008;Farooq, 2011), China (Li, Morgan & Ding, 2008;Yang & Mayston, 2012), Malaysia (Zainizam, 2012(Zainizam, , 2013(Zainizam, , 2014(Zainizam, , 2017Lim, 2013;Zainizam & Battu, 2013;Zulkifly & Hazrul Izwan, 2013) and a comparative study between the State of Mexico, India, the Philippines and Thailand (Mehta, Felipe, Quis & Camingue, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In Developing Countries, to our knowledge, there are only a few studies that have been carried out. These include Mexico (Quinn & Rubb, 2006), Pakistan (Abbas, 2008;Farooq, 2011), China (Li, Morgan & Ding, 2008;Yang & Mayston, 2012), Malaysia (Zainizam, 2012(Zainizam, , 2013(Zainizam, , 2014(Zainizam, , 2017Lim, 2013;Zainizam & Battu, 2013;Zulkifly & Hazrul Izwan, 2013) and a comparative study between the State of Mexico, India, the Philippines and Thailand (Mehta, Felipe, Quis & Camingue, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As overeducation will bring inefficiency in the labour market and pose detrimental effects to individuals, firm and country as a whole such as lowering individual income levels (Sicherman, 1991;Zainizam et al, 2014), happiness (Lim, 2013), health, well-being and life satisfaction (Piper, 2015;Friedland & Price, 2003), influence job satisfaction (Ortiz, 2010) and a signal of productivity loss (Boll, Leppin & Schomann, 2016), it is therefore timely to examine the extent of overeducation among Malaysian graduates by providing a descriptive analysis using a Job Analyst Method of measurement and data from the Graduate Tracer Study (GTS). Since all previous studies in Malaysia only concentrated on self-perceived method, for instance, a study that has been carried out by Zainizam (2017Zainizam ( , 2012, Lim (2013) and Zulkifli and Hazrul Izwan (2013), this study is expected to contribute to the literature through the use of a Job Analyst Method measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Even before the onslaught of the pandemic on Malaysian soil, job seekers and young graduates experienced difficulties in securing their desired jobs (Hanapi & Nordin, 2014;Ismail, 2011). There was also a mismatch between workforce demand and talent supply in Malaysia (Misni et al, 2020;Sulaiman, & Ismail, 2019, Zakariya, 2017. Therefore, amidst the challenging global environment, both employees and organisations must innovate, rebrand, and reposition themselves to stay relevant.…”
Section: Introductionmentioning
confidence: 99%
“…The massification of higher education (Mok and Jiang, 2018; Tight, 2017) has resulted in more graduates pursuing a limited number of available vacancies. The intense competition may well lead to graduates accepting any available position in order to take those first steps into the workplace, and it has been it is found that some graduates are mismatched with their jobs (Mavromaras et al, 2013; Steed, 2018; Zakariya, 2017). Alternatively, graduates may delay their entry into the jobs market by seeking additional academic awards.…”
Section: Introduction – the Competitive Uk Graduate Jobs Marketmentioning
confidence: 99%